Persepsi Masyarakat terhadap Vaksinasi Booster Covid-19 di Wilayah Tanjung Priok Jakarta Utara - Samosir, David Caesar Yusuf; Yenny, Yenny; Pangaribuan, Santa Maria (Jurnal Kesehatan, 2023)
Covid-19 is a group of viruses that cause disturbances in the respiratory tract organs. Indonesia's government has promoted various interventions, known as health protocols, to prevent the spread of Covid-19, such as using masks, washing hands, and vaccinations. The emergence of different perceptions from the public makes the Covid-19 vaccination problem. Doubts arose about the safety and usefulness of Covid-19 vaccines, resulting in a poor perception of this vaccination program. This study aims to identify the public's perception of the Covid-19 booster vaccination in the Tanjung Priok area, North Jakarta. This research design is descriptive and quantitative. The population study is residents of RW 015 Tanjung Priok, North Jakarta, with a total of 6500 people. The number of samples is determined by the solving formula as many as 119 respondents. The selection of the samples in this study used convenience sampling. The research instruments have been tested for validity and reliability. The analysis used is descriptive quantitative. The results showed that most respondents in the Tanjung Priok area of North Jakarta negatively perceived the Covid-19 booster vaccination. The conclusion from this study is that the people of the Tanjung Priok area in North Jakarta have a negative perception of the Covid-19 booster vaccination, so it is expected that the public will continue to seek information regarding the Covid-19 booster vaccination to increase a more positive perception of the Covid-19 booster vaccination.